FROM SOCIAL POLICY TO TAX POLICY. RETURN TO THE PAST - L. Kramarenko; A. Lukashevich (Вестник университета)
The article discusses changes made in the system of obligatory social insurance, the inclusion of obligatory social insurance payments to the Tax code of the Russian Federation, consolidation of the tax authorities control functions. insurance and tax mechanisms for the formation of the state non-budgetary funds. A comparative analysis of the structure of the pension system in Russia and abroad. Special attention is paid to the advantages and disadvantages of innovations. Analyzes problems encountered by taxpayers and payers of social insurance payments in connection with the innovations.